غَلبة المصطلحِ البصريّ في الدرسِ اللّغوي قراءةٌ في الخلاف وأسبابه - حريز محمد, تغريد (Al-Adab Journal, 2018)
Talking about the grammatical terms is linked to the beginnings of grammar establishment . The tales that being submitted at that time included grammatical terms have not included but preliminary signs of grammar science . The tales indicated that Aba Al-Ausud had submitted a terms that is coming to be known as " The spots " . This indicated on the movements of indications and "al Tanwein" term . The hear and scale in view point of Basra residents had been different , since Basra , owing to its geographical location on Arab Gulf , makes the process of mixture with non- Arabs is an easy process. This , in return , make Basra residents searched for accuracy in linguistic hearing in addition to other scales. The studies have proved the dominance of Basra term than Kufi term , in addition to other doctrines such as Al-Baghdadi sect . This current study is to clear out this dominance and the source of the strength in the Basra subject via an introduction to the grammatical term that is of two axes : the 1st one : includes reasons of Basra term dominance and the 2nd one ; the balance between the Basra term and others